Brochoscopic cryoablation of a large endobronchial chondroid hematoma presented as right middle lobe collapse in a 63 years old male patient (Journal of Bangladesh College of Physicians and Surgeons, 2024)
Chondroid hamartoma is the most common benign tumor of lung, which account 8% of pulmonary neoplasm. Most often they are seen peripherally in the lung parenchyma. But very rarely it can originate endo-bronchially and present as collapse of lung or lobe. To be precise less than 10% cases was reported to be found. Here we mention a case of endo-bronchial chondroid hamartoma in a 63 years old gentleman presented as right middle lobe collapse and was diagnosed after repeated attempts of bronchoscopic biopsy or trans-thoracic fine needle aspiration. The tumor was removed by bronchoscopic cryo-debulking of the mass almost completely instead of thoracotomy resection or APC laser ablation.J Bangladesh Coll Phys Surg 2024; 42: 292-296